Transcarpathian region is the best place to invest in the future - Pylyavskyy, Yuriy (My University, 2014)
Transcarpathian Region is bordered by Romania to the south, Hungary to the southwest, Slovakia to the west, and Poland to the northwest. It is thickly forested and largely agricultural. The plain in the southwest, which is drained by the Tisza River and its tributaries, supports crops of wheat, com, tobacco, sugar beets, and potatoes. There are vineyards, fruit orchards, and walnut groves in the foothills. The region's mineral resources include brown coal, rock salt, fire clays, marble, and limestone. Forests occupy nearly half the area of the oblast, and lumbering, along with the production of such items as wood chemicals, furniture, and cartons, is a leading industry. The majority of the population is Ukrainian, with Hungarian, Russian, Slovak, and Rusyn minorities.
Keywords: investment policy; budget; Transcarpathian region; інвестиційна політика; бюджет; Закарпатська область; инвестиционная политика; Закарпатская область